1995
DOI: 10.1177/174182679500200607
|View full text |Cite
|
Sign up to set email alerts
|

Precursors of Atherosclerosis in a Random Sample from a Hellenic Population: The Athens Study

Abstract: Background: Atheromatosis, the principal lesion in atherosclerotic cardiovascular disease, is associated with increased levels of blood pressure, serum cholesterol, cigarette smoking and other variables. As these lesions are thought to appear first in childhood, this study was designed to assess the levels of these atherosclerotic precursors in children living in Athens, Greece. Methods: The following parameters were measured in a random sample of 411 7 school children aged 6-18 years, living in the centre of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
2
1
Order By: Relevance
“…Mean BMI (20.4 ± 3.5 kg m )2 ) and the prevalence of overweight (30%) and obesity (7%) in Volos children were quite high, similar to or even greater than those reported previously for young adolescent populations living in other areas of Greece, whether urban or rural (Adamopoulos et al, 1995;Mamalakis & Kafatos, 1996;Mamalakis et al, 2000;Krassas et al, 2001a,b;Karayiannis et al, 2003;Magkos et al, 2005). Nevertheless, a note should be made of the fact that overweight and obesity prevalence rates reported in the other studies of Greek children and adolescents are not all based on the IOTF criteria.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Mean BMI (20.4 ± 3.5 kg m )2 ) and the prevalence of overweight (30%) and obesity (7%) in Volos children were quite high, similar to or even greater than those reported previously for young adolescent populations living in other areas of Greece, whether urban or rural (Adamopoulos et al, 1995;Mamalakis & Kafatos, 1996;Mamalakis et al, 2000;Krassas et al, 2001a,b;Karayiannis et al, 2003;Magkos et al, 2005). Nevertheless, a note should be made of the fact that overweight and obesity prevalence rates reported in the other studies of Greek children and adolescents are not all based on the IOTF criteria.…”
Section: Discussionsupporting
confidence: 81%
“…Likewise, such an activity pattern has been associated with a more favourable cardiovascular and metabolic risk profile among children 9-18 years old (Katzmarzyk et al, 1999). Despite the fact that children of the present study devoted more time on MVPA and less time on TV/ PC compared to their peers living in other Greek regions, still, they displayed similar or increased prevalence of overweight and obesity (Adamopoulos et al, 1995;Mamalakis & Kafatos, 1996;Mamalakis et al, 2000;Krassas et al, 2001a,b;Karayiannis et al, 2003;Magkos et al, 2005), and exhibited a worse blood lipid profile (Aravanis et al, 1988;Petridou et al, 1995;Schulpis & Karikas, 1998;Mamalakis et al, 2001;Ferro-Luzzi et al, 2002;Manios et al, 2002;Magkos et al, 2005). The reasons for this are unclear at present, and illustrate the need to study this population using a larger sample to confirm and further investigate the present intriguing findings.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…In Greece, previous studies in children and adolescents have suggested an especially high prevalence of elevated BP with rates even in the range of 20 % -30 % in the studied populations (9,21,72,73) . However, these results should be interpreted with caution, since confi rmation of hypertension requires repeated BP measurements in multiple visits, a fact that is probably responsible for overestimation of hypertension rates (39,65,67,74) .…”
Section: Metabolic Consequences Of Obesitymentioning
confidence: 72%